OFR-10-78 Capital And Operating Cost Estimating System Handbook. Mining And Beneficiation Of Metallic And Nonmetallic Minerals Except Fossil Fuels In The United States And Canada - George K. Clement (The National Institute for Occupational Safety and Health (NIOSH), 1978)
Manual estimating method through use of equations, factors and curves for preparation of feasibility type estimates for capital and operating cost of mining and primary beneficiation in the United States and Canada of various types of minerals occurrences, except fossil fuels, using state-of-the-art technology. User should have basic estimating experience in the mining industry and/or related fields. Primary usage of this handbook will be for the preparation of preliminary estimate within a reasonable degree of accuracy with relative small amounts of hard input data. Output may be used to determine if a more finite type of estimate should be produced.